Review of the globally invasive freshwater mussels in the genus Sinanodonta Modell, 1945 - Karel Douda; Alexandra Zieritz; Barbora Vodáková; Maria Urbańska; Ivan N. Bolotov; Jana Marková; Elsa Froufe; Arthur E. Bogan; Manuel Lopes-Lima (Hydrobiologia, 2025)
In this review, we synthesize the current knowledge of the biology, ecology, and impact of Sinanodonta freshwater mussels (Bivalvia, Unionidae), native to East Asia, that have successfully invaded Europe, Central America, North Africa, and several Asian regions. The main introduction pathways of Sinanodonta were reconstructed based on DNA sequence data and distribution records. We show that invasive lineages of Sinanodonta belong to three species, namely, S. woodiana s. str. (“temperate invasive” lineage), S. pacifica (“tropical invasive” lineage), and S. lauta . Their generalist fish-dispersed larvae, short life span, high fecundity, use by humans for multiple purposes, and ability to establish populations in anthropogenically disturbed conditions were identified as crucial traits driving their invasions. Information on the consequences is scarcer, but Sinanodonta can impact native species through larval parasitism, host fish/food competition, and parasite transmission. In addition, ecosystem effects through their filtration—biodeposition—excretion activity and the occurrence of massive die-offs were detected. Ecosystem services and disservices have not yet been quantified, even at local scales, and management methods in the invasive range are understudied. A better understanding of Sinanodonta ecology, impacts, and management options is urgently needed to make informed decisions and set realistic and impactful restoration goals.